Strength behaviour of sandstone subjected to polyaxial state of stress - Saurav Rukhaiyar; Narendra Kumar Samadhiya (International Journal of Mining Science and Technology, 2017)
The paper presents an experimental investigation on the strength behaviour of natural rock subjected to polyaxial state of stress. The polyaxial tests were conducted on cubical specimens of sandstone obtained from the Shivpuri district in Madhya Pradesh state of India. The specimens having nominal dimensions of 100 mm × 100 mm × 100 mm were tested using a polyaxial testing machine. Twenty-five combinations of intermediate and minor principal stresses were applied and the specimens were loaded till failure occurs. It was observed that the intermediate principal stress has a substantial effect on the strength of the Shivpuri sandstone. A database of rock strength under various combinations of σ2 and σ3 was obtained for the Shivpuri sandstone. The database was used to study the predictability of five most commonly used strength criterion. Root mean square error (RMSE), average absolute relative error percentage (AAREP) and coefficient of accordance (COA) were used as indices for the measure of goodness of fit. It was observed that the least error in the prediction was shown by modified Mohr Coulomb criterion followed by modified Weibols and Cook criterion. A probability analysis of the error in prediction was also done. Keywords: Polyaxial testing, Sandstone, Strength criterion, Modified Mohr-Coulomb criterion, Modified Weibols and Cook criterion